IMPLEMENTASI WORK–LIFE BALANCE DALAM PEMELIHARAAN SDM: ANALISIS YURIDIS MANAJERIAL DAN KERANGKA REGULASI PADA PT PLN (PERSERO) - Ferizko, Adia; Widia, Janeska; Aulia Azfa, Rafi; Fany Caroline Sihombing, Jane; Sakinah Amin, Mutia (Pahlawan Tuanku Tambusai University, 2025)
IMPLEMENTASI WORK–LIFE BALANCE DALAM PEMELIHARAAN SDM: ANALISIS YURIDIS MANAJERIAL DAN KERANGKA REGULASI PADA PT PLN (PERSERO) Human resource (HR) maintenance is a strategic function in modern management aimed at preserving employee well-being, loyalty, and productivity. Challenges such as high employee turnover, work-related stress, and work–life imbalance require organizations to implement comprehensive maintenance strategies. This study aims to examine the concepts, objectives, and methods of human resource maintenance through a literature review approach and to analyze its implementation at PT PLN (Persero). The research employed a Systematic Literature Review (SLR) method on scientific articles published between 2020 and 2025, complemented by document analysis of PT PLN (Persero) Annual Report 2024. The findings indicate that work–life balance (WLB), occupational safety and health, compensation systems, as well as employee welfare and competency development programs are key factors in improving employee engagement and retention. Practices at PT PLN demonstrate strong alignment with modern HR management theories through the implementation of SMK3 with a Zero Accident target, internalization of AKHLAK core values, and strengthening of employee well-being initiatives. This study concludes that integrated HR maintenance not only enhances employee welfare but also significantly contributes to organizational sustainability and competitiveness. Keywords: Human Resource Maintenance, Work–Life Balance, Employee Well-Being, Retention, PT PLN.